Long-term efficacy of deep brain stimulation for essential tremor: An observer-blinded study. (19th March 2019) - Paschen, Steffen; Forstenpointner, Julia; Becktepe, Jos; Heinzel, Sebastian; Hellriegel, Helge; Witt, Karsten; Helmers, Ann-Kristin; Deuschl, Günther
Abstract : Objective: Deep brain stimulation (DBS) of the ventral intermediate thalamic nucleus (Vim) is established for medically refractory severe essential tremor (ET), but long-term efficacy is controversial. Methods: Twenty patients with ET with DBS had standardized video-documented examinations at baseline, in the stimulation-on condition at short term (13.1 ± 1.9 months since surgery, mean ± SEM), and in the stimulator switched on and off (stim-ON/OFF) at long term; all assessments were done between 32 and 120 months (71.9 ± 6.9 months) after implantation. The primary outcome was the Tremor Rating Scale (TRS) blindly assessed by 2 trained movement disorder neurologists. Secondary outcomes were TRS subscores A, B, and C; Archimedes spiral score; and activities of daily living score. At long-term follow-up, tremor was additionally recorded with accelerometry. The rebound effect after switching the stimulator off was assessed for 1 hour in a subgroup. Results: Tremor severity worsened considerably over time in both in the nonstimulated and stimulated conditions. Vim-DBS improved the TRS in the short term and long term significantly. The spiral score and functional measures showed similar improvements. All changes were highly significant. However, the stimulation effect was negatively correlated with time since surgery (ρ = −0.78, p < 0.001). This was also true for the secondary outcomes. Only one-third of the patients had a rebound effect terminated 60 minutes after the stimulator was switched off. Long-term worsening of the TRS was more profound during stim-ON than in the stim-OFF condition, indicating habituation to stimulation. Conclusion: Vim-DBS loses efficacy over the long term. Efforts are needed to improve the long-term efficacy of Vim-DBS. Classification of evidence: This study provides Class IV evidence that for patients with medically refractory severe ET, the efficacy of Vim-DBS severely decreases over 10 years.